KETENTUAN HUKUM PADA PERLINDUNGAN KORBAN KEJAHATAN DI INDONESIA (Faculty of Law, University of Palembang, 2023)
If a criminal act or crime occurs where the consequences of the act result in a crime victim, provisions are needed which aim to provide protection to regulate and protect the crime victim so that the crime victim gets their rights protected. To balance this, a regulation is needed that regulates the protection of crime victims. The research method used is normative legal research. Legal material obtained from secondary data is collected by means of literature study and then analyzed using qualitative analysis. A legal system does not only consist of norms but also institutions. Institutions that specifically provide protection rights to witnesses and victims as a form of fulfilling the rights of witnesses and victims